ANALISIS FAKTOR YANG BERPENGARUH TERHADAP TINDAKAN PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rosida Maedina (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This study aims to determine the effect toto profitability, financial risk, the size of the companies either partially or simultaneously on income smoothing practices. The method of analysis used is multiple regression analysis is a linear relationship between two or more independent variables X1, X2, X3, X4 and dependent variable Y. While the results of this study indicate the financial risk variables have a significant positive relationship and not on income smoothing because financial risk on the regression coefficients have a value hypothesis testing positif.Variabel sized companies have a significant positive relationship and not on income smoothing because the regression coefficient of firm size in hypothesis testing has value positif.Secara simultaneously be concluded that the variable profitability, financial risks, and the size of the company together - together (simultaneously) did not have a significant effect on income smoothing for F arithmetic <F table.